Las funciones básicas y el desarrollo de la pre-escritura en los niños de primer año de educación básica, paralelo “c” de la unidad educativa fiscomisional “Santo Tomás Apóstol”, de la cuidad de Riobamba, provincia de Chimborazo, en el año lectivo 2014 – 2015 - Muñoz Pérez, Ana Francisca (2016)
The development of the basic functions plays a key role because it is through this will promote changes in attitudes and behavior in children capable of generating a wider view of the word and the possibility of satisfying needs and find a solution to the problems there are presented to them. From this perspective it is considered that the basic functions have been a priority that should be assumed in a responsible way in the search for efficient results in the teaching-learning process, it is, therefore, necessary to consider alternatives that will contribute to the achievement of the objectives and goals that this challenge requires demands from us. That is why has been detected that children First –Year Basic Education, present problems within the basic functions, such as lack of motor coordination, laterality, spatial tempo orientation, is for this important considerations make this investigation determine actions they will contribute to the development and welfare of children, the subject of this research work. The instruments used consisted observation sheets applied to children in the first year of basic education. The data analysis carried out, consisted of categorizing records and the contents of observation. The results confirm that indeed, the basic functions directly affect the meaningful learning of children in the first year of basic general education of the Educational Unit “Santo Tomás Apóstol” of the City of Riobamba.